2011
DOI: 10.1021/cm2006956
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Oxygen Storage Capacities of Hexagonal Dy1–xYxMnO3+δ

Abstract: Polycrystalline samples of hexagonal P63 cm (space group No. 185) Dy1–x Y x MnO3+δ were synthesized over complete solubility ranges under reducing conditions with oxygen partial pressures of 5 ppm to air at high temperatures (1200–1400 °C). All samples displayed unusually large, reversible oxygen content excess (0 ≤ δ ≤ 0.35) at low temperatures of ∼200–400 °C under air and oxygen atmospheres in thermogravimetric measurements. During heating, stoichiometric samples showed rapid uptakes of oxygen at 200–300 °C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
70
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(83 citation statements)
references
References 51 publications
8
70
0
Order By: Relevance
“…14), which coincides with a maximum in electrical conductivity. The deviation in conductivity from the exponential behaviour of a semiconductor stems from the different temperature dependence of the concentration and mobility of holes.…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…14), which coincides with a maximum in electrical conductivity. The deviation in conductivity from the exponential behaviour of a semiconductor stems from the different temperature dependence of the concentration and mobility of holes.…”
Section: Resultsmentioning
confidence: 75%
“…Oxygen vacancies in YMnO 3 have been studied111213, and large oxygen excess has been reported for h- R MnO 3+ δ ( R =Y, Dy) with δ up to 0.35 for R =Dy14. High levels of excess oxygen can cause development of secondary oxidized phases, which are easily detected experimentally15.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Early reports showed that the ionic size or the cell volume strongly affects the oxygen release properties. 6,10,11 However, as shown in Figure 9a, for the doping in Ca 2 MnAlO 5+δ no apparent correlation exists for any trend. This is probably because the dopants at different sites behave significantly differently.…”
Section: ■ Discussionmentioning
confidence: 88%
“…Due to the oxygen storage and release capacity of YMnO 3 -related system [18], here we use electron beam irradiation to drive the motion of oxygen vacancy under the vacuum environment of a transmission electron microscope (TEM). As a result, the ordered arrangements and high mobility of V O s are identified by selected area electron diffractions (SAED); the corresponding structural models and possible evolution route are proposed.…”
Section: Introductionmentioning
confidence: 99%